Allelochemicals from Castanea Sativa Mill.: Plant-Root Environment Interactions - Pavliuchenko, Nataliia; Grygorieva, Olga; Klymenko, Svitlana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The paper is devoted to the study of the allelopathic properties of the root environment of Castanea sativa Mill. plants of different ages under the conditions of introduction. The objects of the research were 10 and 40-year-old plants of C. sativa, which are growing in Forest-Steppe of Ukraine in M.M. Gryshko National Botanical Garden of National Academy of Sciences of Ukraine. Rhizosphere soil samples were collected at 0–30 cm layer. The fallow soil was used as a control. Allelopathic and biochemical analyzes of root environment of C. sativa were conducted in dynamics during the growing season. Allelopathic activity of the root environment was studied by direct bioassay method. The soil redox potential (Eh) was measured by potentiometric technique. Phenolic compounds were extracted from the soil by desorption method using an ion exchanger KU-2-8 (H+). Allelopathic analysis of the root environment of chestnut plants showed phytotoxicity within the range of 19.9–61.9 % compared with control. Phytotoxicity increased under the influence of 40-year-old plants. The redox status of the root environment of C. sativa was characterized by the predominance of reducing conditions, the intensity of which increased under the influence of the older plants. The values of redox potential of the rhizosphere soil were 1.2–3.5 times lower than control. This indicates the accumulation of mobile organic compounds in the root environment of C. sativa. The content of phenolic compounds in the root environment of C. sativa was 1.4–2.5 times higher than control. The accumulation of organic compounds of phenolic nature caused obviously an increase in the phytotoxicity of the root environment of C. sativa along with the age of the plants. Thus, the seasonal dynamics of allelopathic activity, redox conditions, and the content of phenolic allelochemicals in the root environment of C. sativa depended on the age of plants.